A Growing Freshwater Lens in the Arctic Ocean With Sustained Climate Warming Disrupts Marine Ecosystem Function. Issue 12 (19th December 2020) - Fu, Weiwei; Moore, J. Keith; Primeau, François W.; Lindsay, Keith; Randerson, James T.
Abstract: One of the most robust changes in the hydrological cycle predicted by Earth System Models (ESMs) during the remainder of 21st century is an increase in the difference between precipitation and evapotranspiration (P‐E) in arctic and boreal regions. We explore the long‐term consequences of this change for marine ecosystems in the Arctic Ocean using the Community Earth System Model forced with a business as usual scenario of future greenhouse gas concentrations. We find that by the year 2300 increases in freshwater delivery considerably reduce Arctic Ocean surface salinity, creating a freshwater lens that has far‐reaching impacts on marine biogeochemistry. The expanding freshwater lens limits vertical nutrient supply into the euphotic zone by enhancing vertical stratification and accelerating surface lateral mixing with surface waters in the North Atlantic, which become increasingly nutrient depleted from weakening of the Atlantic Meridional Overturning Circulation (AMOC). The resulting increase in nutrient stress reduces marine export production in the Arctic Ocean by 53% in 2300 relative to the 1990s and triggers a shift in community composition with small phytoplankton replacing diatoms. At the same time, the seasonal timing of export production undergoes a 2‐month forward shift, with the peak advancing from July to May. This suggests that the threat to food webs and higher trophic levels may intensify after the year 2100 as gains in productivity from sea ice loss saturate and freshwater impacts on nutrient stress continue to strengthen. Our analysis highlights the critical importance of changing terrestrial hydrology and land‐ocean coupling as drivers of long‐term biogeochemical change in the Arctic Ocean and the necessity of multi‐century climate change projections. Plain Language Summary: Climate warming will cause more rain and snow to fall in northern regions, increasing river runoff and causing the Arctic Ocean to freshen. Using a global climate model, here we explore the long‐term consequences of this freshening for the marine biosphere. As the Earth responds to a future scenario of "business‐as‐usual" fossil fuel emissions, an expanding lens of freshwater will form a cap on the surface of the Arctic Ocean, limiting the upward mixing of nutrient‐rich water from deeper ocean layers. This stunts the growth of phytoplankton, counteracting by 2100 gains in marine productivity caused by increasing light availability from sea ice loss. After 2100, as the freshwater cap strengthens, small phytoplankton mostly replace diatoms in arctic ecosystems as a consequence of increasing nutrient stress. This transition happens rather suddenly, suggesting that the marine biosphere may pass through an ecological tipping point. By 2300, export production, a measure of the flow of organic matter available to support zooplankton, fish, and marine mammals, declines by over 50%. At the same time, a shift in the timing of the peak phytoplankton bloom from July to May is likely to further disrupt arctic food webs. Our work shows that climate change impacts on the hydrological cycle in the far north will have long‐lasting and far‐reaching impacts on the marine biosphere in the Arctic and highlights the importance exploring the potential for ecological tipping points in deep future time. Key Points: A growing lens of freshwater in the Arctic Ocean continues to expand after the year 2100 in CESM1(BGC) for RCP 8.5 The expanding freshwater lens increases nutrient stress, overriding gains in marine productivity associated with sea ice loss By 2300, export production declines by 53% and the peak bloom shifts from July to May, strongly influencing arctic marine food web dynamics